Design and Development of FTTH Network Infrastructure Using GPON Technology in Sukoharjo Regency - Muhammad Alfarezi; Popy Maria; Uzma Septima (International Journal of Wireless And Multimedia Communications, 2025)
Abstract— The increasing demand for high-speed, reliable internet access in the digital era has led to the decline of conventional copper-based networks and the rise of fiber-optic-based solutions. This study focuses on the design and development of a Fiber To The Home (FTTH) network using Gigabit Passive Optical Network (GPON) technology in Banaran Subdistrict, Sukoharjo Regency, an area with growing economic activity, particularly in the Micro, Small, and Medium Enterprises (MSME) sector. The implementation of GPON is seen as a critical infrastructure enhancement that supports regional development, education, and digital connectivity. The research methodology began with site surveys using Google Earth Pro and QGIS to collect spatial data such as household coordinates and pole locations. This data was then processed using Setics Sttar Planner version 2.3.12, enabling automatic calculation of optimal cable routes, equipment locations, and required component specifications. The resulting FTTH design covers four neighborhood units (RW 1, RW 2, RW 4, and RW 5), serving a total of 630 homepasses. Key components of the network include 1 Optical Line Terminal (OLT), 2 Fiber Distribution Terminals (FDTs), 46 Fiber Access Terminals (FATs), and 125 poles. The power link budget calculation, essential to determining signal feasibility, produced theoretical receive power values between -15.089 dBm and -14.144 dBm. Field implementation and post-deployment measurements were conducted in RW 1 and RW 2 to validate the theoretical model. Adjustments were made due to site constraints, including reductions in splitter and FAT counts, as well as cable length modifications. Measured receive power values ranged from -16.71 dBm to -16.22 dBm, which still fall within acceptable standards defined by PT. iForte Solusi Infotek (between -10 dBm and -21 dBm). The differences between calculated and actual measurements were attributed to splicing quality, variations in cable deployment, and environmental factors. Overall, the study successfully demonstrates the feasibility and efficiency of deploying GPON-based FTTH infrastructure in semi-urban regions like Sukoharjo. The integration of digital tools for planning and field validation ensures optimal network performance, supporting the goal of bridging the digital divide and enhancing socio-economic development in the area.